PENGARUH CHANNEL YOUTUBE CNN INDONESIA “ PRESTASI ANAK PEMULUNG “ TERHADAP KEMAMPUAN MENGIDENTIFIKASI TEKS PERSUASI SISWA KELAS 8 SMP NEGERI 58 PALEMBANG - Adelia Piesesha, Ayu; Hetilaniar, Hetilaniar; Wandiyo, Wandiyo (Parataksis: Jurnal Bahasa, Sastra, dan Pembelajaran Bahasa Indonesia, 2023)
The study discusses the influence of CNN Indonesia YouTube Channel “ Prestasi Anak Pemulung " on the ability to identify persuasive texts of 8th grade students of SMP Negeri 58 Palembang. This study was conducted to determine the influence of CNN Indonesia YouTube Channel "Prestasi Anak Pemulung" on the ability to identify persuasive texts of 8th grade students of SMP Negeri 58 Palembang. The reason for this research is because the researchers found several problems, including the lack of innovation in student learning, lack of interest in student learning, monotonous student learning methods and so on. This study uses a type of experimental quantitative research. This research method involves a true experiment by using 2 classes as a sample in the study with a design using 2 groups, namely the experimental group and the control group. Data collection techniques in this study include tests and documentation, with 2 times the pre-test and post-test data collection for 4 meetings. Analysis of usage data of CNN Indonesia YouTube channel "Prestasi Anak Pemulung" using SPSS analysis. The results of this research are expected to be useful for students to be able to learn in a more modern and fun way, for teachers to be able to conduct more elastic learning with the Times, and for future researchers to be inspired to provide other solutions to this problem. Keywords: Influence, YouTube Channel, Persuasion Text, CNN Indonesia, identify